Which methods of dissemination do women in Cape Town, South Africa prefer when searching for safe abortion providers? - Blackburn, Kayla M (Department of Public Health and Family Medicine, 2019)
Background: The Choice on Termination of Pregnancy Act of 1996 makes provision for access to safe abortion, free of charge in government facilities in South Africa. Despite liberal abortion legislation, unsafe abortion persists in South Africa. Increasing access to information about safe and legal abortion providers through methods such as online databases, community health workers, and telephone hotlines will most likely decrease the number of women using illegal/unsafe abortion providers. This study aims to: determine how women prefer to access information on safe abortion providers and services in Cape Town, South Africa; determine which avenues of obtaining information are most accessible for women; and determine if there is a preferential difference in accessing information based on age, education and socioeconomic status. The purpose of this research is to provide knowledge on how to increase the accessibility of safe abortion providers and services through preferential information dissemination. Methods: Participants were recruited from Marie Stopes International South Africa, a non-profit organization (NGO) that provides sexual and reproductive health services in Cape Town, South Africa. Recruitment of participants took place between September and November 2017. Eligibility criteria included that participants be between 18 to 49 years of age and presenting for an abortion. Data was collected through a self-administered paper-based questionnaire. There were four sections of the questionnaire: Socio-Demographics, Reproductive History, Interactions with Sources of Health Information, and Preferred Method to Access Information. Results: Ninety-eight women completed the self-administered questionnaire. Over 59 % of women preferred to use the internet to access information about safe abortion providers. Participants had access to the internet via their mobile phones, computers, laptops, and tablets. Internet access was more accessible for women who had completed secondary school and/or acquired a post-secondary degree, was employed, and/or earned more than USD 258 a month. Participants also preferred to use health care providers (29%), and community health workers (20%) for accessing information about safe and legal abortion services. Conclusions: This study identified the most preferred and acceptable methods to access information about safe abortion providers by women at an NGO clinic in Cape Town. Community health workers, the internet and health care providers and hotlines should be used to formulate dissemination methods that are tailored to women in South Africa. Information about government facilities, their current abortion provision status, and the type of abortion services they provide should be compiled, continually updated, and made available to women in dissemination methods that are most preferred, accessible and acceptable to women. Options for socioeconomically disadvantaged women should be developed in conjunction with Internet-based options for accessing information about safe abortion providers and services.